Reunion Beach [large type] : stories inspired by Dorothea Benton Frank - Henry, Patti Callahan; Hilderbrand, Elin; Trigiani, Adriana; Monroe, Mary Alice; King, Cassandra, 1944-; Norris, Mary, 1952-; Lee, Jacqueline Bouvier; Hagerty, Gervais; Wentworth, Marjory, (Marjory Heath) 1958-; Dupree, Nathalie (Harper Large Print, an imprint of HarperCollinsPublishers, 2021)
"Inspired by the title Dorothea Benton Frank planned for her next book--Reunion Beach--these close friends and colleagues channeled their creativity, admiration, and grief into stories and poems that celebrate this ... woman and her abiding love for the Lowcountry of her native South Carolina--a land of beauty, history, charm, and Gullah magic she ... brought to life in her acclaimed novels"--